STRATEGY OF BUSINESS MANAGEMENT AND AGRIBUSINESS SYSTEM OF BALI CATTLE BREEDING TO IMPROVE FARMERS INCOME - Putri, B.R.T; Suparta, I Nyoman; Sudana, IB; Oka, I G.L. (E-Journal of Animal Science Udayana University, 2014)
A Survey was carried out using questionaires as data collection tools in the Village Breeding Centres (VBC) at 5 regencies in Bali. These VBCs were superviced by Bali Cattle Breeding Centre (BPTU). Locations of this study were selected using purposive random sampling and respondents were selected by stratified random sampling. The respondents consisted of 90 farmers and 10 experts who were chosen from BPTU, Department of Livestock and Animal Health, and Udayana University. Quantitative and qualitative data were drived from primary and secondary data. The data were collected by interview using structured questionairs, indepth interviews, observation, study of literature and documents. The data were analyzed using internal and external analysis, Strengths-Weaknesses-Opportunities-Threats (SWOT) analysis, Quantitative Strategic Planning Matrix (QSPM) analysis, and Interpretative Structural Modeling (ISM) analysis. The aims of this study were to find out the strategy of business manajemen and agribusiness system of Bali catlle breeding in order to improve farmers income. The results showed that eight strategies were found in bali cattle breeding consisted of improvement of calf quality by continous selection and breeding system, certification of selected calves, to built animal feed industry, improving Bali cattle breeding business efficiency, developing one village one product program, built a farmers cooperation, intensifying the extension program, and increasing farmer’s entrepreneurship. The strategy of increasing the entrepreneurship spirit of the farmers was the first priority to create bali cattle breeding enterprise more efficient and improve farmers income. These strategies should be followed by claster system in business of Bali cattle breeding which is supported by the Cluster Agribusiness Management Communication Forum (CAMCF) as facilitator in relationship between farmers and other industries and institutions in the cluster with other industries and institutions in the cluster.